2019
DOI: 10.1115/1.4044399
|View full text |Cite
|
Sign up to set email alerts
|

Mining and Representing the Concept Space of Existing Ideas for Directed Ideation

Abstract: Design innovation projects often generate large numbers of design ideas from designers, users, and, increasingly, the crowd over the Internet. Such idea data are often used for selection and implementation but, in fact, can 1also be used as sources of inspiration for further idea generation. In particular, the elementary concepts that underlie the original ideas can be recombined to generate new ideas. But it is not a trivial task to retrieve concepts from raw lists of ideas and data sources in a manner that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 40 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…The computational concept generation method, the Combinator, employed in the approach produces ideas in a random manner. Although randomness is an essential factor of creativity ( Carruthers, 2011), He et al (2019) has indicated that computer-based random combinations often lead to meaningless outcomes through an empirical study. Controlled computer-based combinations as well as human combinations have higher probabilities in producing novel and feasible outcomes (He et al, 2019).…”
Section: The Data-driven Approach and Discussionmentioning
confidence: 99%
“…The computational concept generation method, the Combinator, employed in the approach produces ideas in a random manner. Although randomness is an essential factor of creativity ( Carruthers, 2011), He et al (2019) has indicated that computer-based random combinations often lead to meaningless outcomes through an empirical study. Controlled computer-based combinations as well as human combinations have higher probabilities in producing novel and feasible outcomes (He et al, 2019).…”
Section: The Data-driven Approach and Discussionmentioning
confidence: 99%
“…It uses a technology space map as the knowledge base, which is constructed based on patent data and enables exploration of technical terms in technology domains. He et al (2019) constructed a semantic network of concepts based on their co-occurrences in a set of one thousand idea descriptions from an online crowdsourcing campaign via Mechanical Turk for reuse to inspire design ideation. concepTe (Acharya and Chakrabarti, 2020) is a decision-making support tool during the conceptual design stage offering aids in the designer's familiar domain, of which the knowledge base is grounded in the domain-agnostic SAPPhIRE model ontology.…”
Section: Semantic Network As Knowledge Bases For Engineering Designmentioning
confidence: 99%
“…For example, network visualizations have been utilized to represent the whole technology space to support innovation and competitive intelligence (Luo et al, 2017(Luo et al, , 2018Sarica, Yan, et al, 2020), show the relations between components and subsystems to evalute designs (He and Luo, 2017;Pasqual and De Weck, 2012;Sosa et al, 2007) and inform design decisions (Kim and Kim, 2012;Sosa et al, 2007), discover the patterns of design activities (Alstott et al, 2017;Cash et al, 2014;Cash and Štorga, 2015), reveal the structure of design document repositories to guide retrievals (Fu et al, 2013;Luo et al, 2021), and represent mind maps (Camburn, Arlitt, et al, 2020;Camburn, He, et al, 2020) and concept networks (Chen et al, 2019;Chen and Krishnamurthy, 2020;Liu et al, 2020;Sarica et al, 2019Sarica et al, , 2021Shi et al, 2017;Song, Evans, et al, 2020;Souili et al, 2015) for design ideation uses. On the other hand, a few studies explored other visualization methods such as word-clouds (He, Camburn, Liu, et al, 2019; based on design description texts. Although one can rigorously read and study a design document or description to discover all the design-related entities and comprehend their relations, such a human process is tedious, labourintensive, and limited by the domain-specific knowledge of the reader.…”
Section: Related Workmentioning
confidence: 99%